Pemberdayaan Kebun PLP Desa Melalui Gerakan Mopomulo Di Desa Saripi Kecamatan Paguyaman - Dewa Gede Eka Setiawan; Larasati Sukmadewi Wibowo (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
This KKN-Thematic Village Building activity aims to (1) Facilitate the village and provide the latest data related to the Village SDGs as a starting point for the formulation of village development plans and (2) Communicate the latest data related to the Village SDGs to the Village Government and submit it at village meetings as material and data. initial for the preparation/revision/development of the Village RPJM and Village RKP.Methods and technology The implementation of the Thematic Community Service Program uses two methods, namely the Survey method and Mentoring. In terms of the achievement of the targeted activities in the Thematic KKN-Development Village activities, the latest data on village SDGs is obtained in accordance with the provisions of the Ministry of Village data collection